FDI Determinants in the Eurasian Economic Union Countries and Eurasian Economic Integration Effect on FDI Inflows - Akhmetzaki, Yerkezhan Zhumakankyzy; Mukhamediyev, Bulat Mintayevich (Economy of Regions, 2017)
The paper examines the potential determinants of foreign direct investment inflows into the region of Eurasian Economic Union, as well as incentives for investment into other neighboring countries. In the first model, the authors test a hypothesis on country specific foreign direct investment determinants for the Eurasian Economic Union region. The results of fixed effects estimation show that gross domestic product, infrastructure development and secondary education enrollment have a positive statistically significant effect on the foreign direct investment inflows into the region. Conversely, the impact of Customs Union on foreign direct investment appeared to be negative. Furthermore, in the second model of the natural experiment, the authors empirically test the hypothesis on Customs Union’s effect on foreign direct investment while controlling for both country and time effects. The model includes evaluating the impact of the policy change on foreign investment inflows. The natural experiment outcome also points to the negative effect of Eurasian economic integration on foreign direct investment inflows. Although the countries of Eurasian Economic Union have relatively business friendly regulations, such procedures as enforcing contracts, resolving insolvencies and dealing with construction permits are time-consuming. For attracting foreign investment, it is advisable to facilitate such procedures and make the process of setting up a new business less onerous. The research can be used as an outline for further examining of Eurasian economic integration and apart from that, the study results can be applied for practical purposes of policy elaboration aimed at stimulating foreign direct investment into the Eurasian Economic Union.